Hubungan antara Self-Efficacy Dengan Stres Kerja pada Guru SLB N 1 Bukittinggi - Meroza, Itsmi; Tria Ningsih, Yuninda (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
The research is to recognize correlation between self-efficacy and work stress in Teachers SLB N 1 Bukittinggi city. The reserach design used the quantitative correlation. Population of this study is teachers of children with special needs. The number of samples in this study were 33 teachers. taken through total sampling techiques. This study used self-efficacy scale from Bandura and work stress scale from Robbins as an research measurement. Data gathered is carried out using scale of self-efficacy with 38 items and scale of work stress with 51 item which are arranged based on the Likert scale. Technical analysis use analysis product moment from Pearson.The result has a correlation of -0,399 with a value p = 0,022 (pË‚0,05), it means that there is a negative correlation in high significant between self-efficacy and work stress in teachers